2015
DOI: 10.1007/978-3-319-13761-2_28
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Sequelae from Acute Kidney Injury: Potential Mechanisms for the Observed Poor Renal Outcomes

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2015 and co-published as a series in Critical Care. Other articles in the series can be found online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…This is independent of renal-function recovery, based on routinely used parameters such as serum-creatinine (SCr) levels or estimated glomerular filtration rate (eGFR) (9). Further to this, AKI is an important contributor towards development of Chronic Kidney Disease (CKD) (10). AKI-related treatment cost is significant; in the United Kingdom (UK) alone, AKI-treatment costs £620 million annually (11).…”
Section: Introductionmentioning
confidence: 99%
“…This is independent of renal-function recovery, based on routinely used parameters such as serum-creatinine (SCr) levels or estimated glomerular filtration rate (eGFR) (9). Further to this, AKI is an important contributor towards development of Chronic Kidney Disease (CKD) (10). AKI-related treatment cost is significant; in the United Kingdom (UK) alone, AKI-treatment costs £620 million annually (11).…”
Section: Introductionmentioning
confidence: 99%
“…Effectively controlling the pathogenesis of CKD, such as chronic glomerulonephritis, diabetic nephropathy, lupus nephritis, hypertensive nephropathy, and interstitial nephritis, has a clearly protective effect on delaying the progress of CKD. Recently, many studies have indicated that AKI could also induce CKD [16][17][18][19][20][21]. Patients with mild to moderate AKI often experience "adaptive repair" with repaired kidney function, while patients with severe AKI often bear "maladaptive repair" resulting in reduced kidney function.…”
Section: Discussionmentioning
confidence: 99%